Applying virtual reality to sail education: an innovative strategy to enhance knowledge learning for student novices - Shan Zhao; Fa Ji; Fa Ji (Frontiers in Psychology)
BackgroundSailing has been proved beneficial for physical and mental health promotion, which has made it a prevalent sport among children and adolescents. Nevertheless, the existing pedagogical strategies cannot satisfy students’ demands for learning. To bridge this gap, virtual reality (VR) is considered an innovative approach to addressing the challenges in sailing education.ObjectiveThe study aimed at designing an education program to examine effectiveness of VR technology in sail knowledge learning.MethodsUniversity students with no prior experience or knowledge in sailing were recruited and randomly allocated to either experimental group (N = 32) using VR in lectures and self-practice or control group (N = 34) attending traditional lectures. The sail education program consisted of 12 sessions over 6 weeks. Sailing knowledge test was developed from an official manual by American Sailing Association to assess outcomes of learning in overall performance, sailboat structure, sailing skills, and navigation rules. The Situational Motivation Scale (SIMS) was used to assess the constructs of intrinsic motivation, identified regulation, external regulation, and amotivation. A 2 × 2 MANOVA was conducted for statistical analysis.ResultsBoth groups improved accuracy rate after the program, with significant time effects in all outcome measures. Particular advantages of VR were identified in facilitating knowledge learning on sailing skills and navigation rules. Significant interaction effects suggest that application of VR induced greater improvement than traditional lectures. Comparable performance between the two groups was found in sailboat structure, with non-significant results in group effect and interaction effect. What’s more, VR could better improve students’ intrinsic motivation and identified regulation while better reduce external motivation and amotivation in sailing lessons.ConclusionThe findings verified feasibility of applying VR to promote sail education for student novices. To enhance effects of VR in teaching and learning, course design should focus on reflective connections between knowledge and experience, which stimulate students in active, engaging, and insightful learning.